STRATEGI PEMERINTAH GAMPONG DALAM PEMBERANTASAN NARKOBA (Studi Gampong Matang Peupanji Kecamatan Lhoksukon Kabupaten Aceh Utara) - Ishak, Thanthawi; Miswar, Miswar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
Drug trafficking is still rampant in the jurisdiction of the Lhoksukon Police. Several sub-districts in the city center are often used as places for transactions for these illicit goods. This is where the function and strategy of the Gampong Matang Peupanji Government as a representative of the North Aceh Regency government apparatus, especially regarding the implementation of the right strategy in the field is here. The purpose of the study was to determine the strategy of the gampong government in eradicating drugs in Gampong Matang Peupanji, Lhoksukon District and to find out the obstacles or obstacles faced by the gampong government in its efforts to eradicate drugs. The research methodology is to use qualitative research with a descriptive approach. The results of the study obtained data that the strategy of the Matang Peupanji Gampong Government in its efforts to eradicate drugs was first by compiling the Gampong Qanun or